High-yielding Climate-resilient beans improve food security and kick-start business in Zimbabwe - Pan-Africa Bean Research Alliance (Pan-Africa Bean Research Alliance, 2020)
Agriculture used to be at the center of Zimbabwe’s economy, accounting for about 20% of GDP. But it has since declined to about 10%, since the introduction of the land reform bill. The government has been intensifying efforts to prioritize the sector until 2020. The mostly rural population depend on agriculture, which provides 60-70% of the population with income. Yet smallholder farmers face significant challenges. Low and erratic rainfall, drought, low and declining soil fertility result in widespread poverty and recurring food insecurity. Chronic malnutrition and stunting remain major threats, where less than 10 percent of children aged 6–24 months consume the minimal acceptable diet. Beans as a staple crop provide important protein and can improve income and food security. Yet production dropped 67% between 2010 and 2015, with drought, disease and lack of technology, combined with the transition from large-scale commercial farming to a small scale cropping following land reform in the country, hitting communities hard. The flagship project: “Improving food security, nutrition, incomes, natural resource base and gender equity for better livelihoods of smallholder households in sub-Saharan Africa,” between 2015 and 2020 supported by the Swiss Agency for Development Corporation (SDC) and Global Affairs Canada (GAC), sought to rectify this drop. Partnership between the government’s Department of Research and Specialist Services (DR&SS) and private companies boosted volumes of high-quality seed of high-yielding, climate resilient and market preferred bean varieties from 520 tons in 2015 to 1,840 tons in 2019. Quality bean seed was more available to 1,110,485 farmers in 2019, who also now have better links with markets, more opportunities to sell beans and a better understanding of crop management options like fertilizer use which can increase yields. Project partners have also worked with national researchers to strengthen capacity, ensuring more beans are bred to withstand local challenges like drought, while educating communities of their benefits and scaling up their seed production and access.